Winteruni 2019: Studgorodok* Transformation of the campus in Irkutsk. The program of cultural, socio-economic and spatial development - Nujansina, Valeria; Kostrubova, Alexandra; Kosolapova, Anastasia; Arefev, Danil; Arustamyan, Margarita; Cárdenas, Luigi Barraza; Bursa, Otakar; Gelsenlichter, Julian; Verma, Nikita; Gladkova, Ekaterina; Deutsch, Odysseas; Ilicheva, Svetlana; et al. (project baikal, 2019)
The article tells about the strategy of Winter University of Urban Planning and the characteristics of Winter University of Urban Planning 2019, as well as the experts, pilots and participants of the workshop. The practice-oriented approach of the workshop and the value of the campus have made the Winter University a platform for interesting discussions and innovative proposals.